Use of explicit FEM models for the structural and parametrical analysis of rockfall protection barriers. (1st July 2018) - Castanon-Jano, Laura; Blanco-Fernandez, Elena; Castro-Fresno, Daniel; Ferreño, Diego
Highlights: Finite element packages are essential tools in the study of large and complex structures. The calibration of two barrier models were successfully developed. It was determined that barrier IBT-150 have unnecessary upstream brakes. Four geometric parameters are varied to investigate their influence in the barriers' maximal energy capacity. Abstract: This paper illustrates the experimental test procedure and results of two flexible barriers of low and medium energy, the so-called IBT-150 and IBT-500. For this purpose, ETAG 027 European Guideline is used. All the requirements for the tests performance are followed and the two energy-level tests performance requirements have been fulfilled in both rockfall barriers. Numerical modelling helps to understand and predict the behavior of these barriers with different configurations drastically reducing the costs of performing real tests. The results of the real test on IBT-150 and IBT-500 have been taken as references to validate two numerical models using Abaqus Explicit software. Afterwards, a presentation of some alternatives of the barrier IBT-150 are stated, which allow a more economical design removing some components that do not affect the energy level of 150 kJ set by the manufacturer. Also, a parametrical analysis of the IBT-500 numerical model has been performed varying the geometrical characteristics, such as the net grid dimension, the diameter of the perimeter cable, the length of the functional modules and its height. The aim of this analysis is the enhancement of maximum energy capacity of the barrier related with the amount of material used to build it. Following the ETAG recommendation, the maximum energy level (MEL) test is achieved if the barrier is able to retain the block. Thus, the MEL level for each numerical model was determined by increasing the initial speed of the block until it trespasses the barrier.